An analytical method to determine the fluid-rock heat transfer rate in two-equation thermal model for EGS heat reservoir. (October 2017) - Huang, Wenbo; Cao, Wenjiong; Guo, Jian; Jiang, Fangming
Highlights: An analytical solution to heat transfer in fractured porous rock is derived. The rock-fluid heat transfer rate in EGS reservoirs is analytically estimated. Using the analytical solution increases the prediction accuracy of numerical model. Numerical model becomes more viable for industry-scale EGS simulations. Abstract: The two-equation thermal model could be an effective method for the simulation of thermal-hydrodynamic process in industry-scale EGS heat reservoirs. The conventional way of computing the heat transfer rate between rock and fluid in the two-equation model is using Newton's law of cooling with a constant equivalent solid-fluid heat transfer coefficient. However, the present work reveals that this method is unable to precisely simulate EGS heat extraction, in which the thermal resistance of solid plays an important role and the temperature of fluid is in rapid changing. Instead, we propose an analytical method to determine the heat transfer rate between rock and fluid, in which variations of fluid and rock temperatures are adequately considered. Simulation cases with different meshes or using different thermal models corroborate that the proposed method improves the prediction accuracy of the two-equation model and makes the model to be more applicable for industrial-scale EGS simulations as a larger mesh size is allowed to be used in the simulation.